A study on the effect of interelectrode gap in the electrochemical additive manufacturing process. Issue 2 (4th March 2019) - Sundaram, Murali; Drexelius, Amy; Kamaraj, Abishek B.
Abstract: Electrochemical additive manufacturing (ECAM) is achieved by localized electrochemical deposition (LECD). The ECAM can print metal parts directly from computer models at macro-, micro- and nanoscales at room temperature without any thermal defects. This study aims to (1) simulate the effects of the interelectrode gap (IEG) on cation concentration and current density in the deposition zone during ECAM; (2) quantify the localization of the desired deposit, as well as unintended plating when using various IEGs, and (3) determine the rate of deposition for different IEGs. Current density patterns under stationary and moving anode conditions were analyzed to calculate deposition rate and the corresponding time to fill an IEG. Experiments were performed to monitor current density and time to fill IEG during deposition and compared with the simulation results. Studying the migration behavior of cations and the current density allowed deposition height to be predicted and the extent of plating to be quantified, using a distortion factor. It was found that for the ECAM conditions used in this study, smaller IEGs (<10 µm) result in lower rates of deposition due to the cation depletion, while larger IEGs (50 µm) result in an increase in plating tendency due to cation migration.